Empowering a local community to address climate risks and food insecurity in Lower Nyando, Kenya - Macoloo C; Recha, John W.M.; Radeny, Maren A.O.; Kinyangi, James (2013)
In erosion- and drought-prone Nyando, self-help groups affiliated to large umbrella bodies are working with extension agents, researchers and development partners to improve local livestock and diversify crops, to improve soil and water management, and to pool financial and labour resources.